2022
DOI: 10.53730/ijhs.v6ns3.5189
|View full text |Cite
|
Sign up to set email alerts
|

In silico ADMET analysis, Molecular docking and in vivo anti diabetic activity of polyherbal tea bag formulation in Streptozotocin-nicotinamide induced diabetic rats

Abstract: Ichnocarpus frutescens, Ficus dalhousie, Crateva magna, Alpinia galangal, and Swertia chiraita are well-known plants available throughout India and they are commonly used for the treatment of various diseases including diabetes mellitus. The antidiabetic activity of the individual plant parts is well known, but the synergistic or combined effects are unclear. Polyherbal formulations enhance the therapeutic action and reduce the concentrations of single herbs, thereby reducing adverse events. The aim of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Antioxidant activity of polyherbal formulation has been calculated by the DPPH radical scavenging assay [ 24 ], the GTA (green tea antioxidants) activity [ 25 ], and by using the thiobarbituric acid reactive substance assay (TBARS) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant activity of polyherbal formulation has been calculated by the DPPH radical scavenging assay [ 24 ], the GTA (green tea antioxidants) activity [ 25 ], and by using the thiobarbituric acid reactive substance assay (TBARS) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…JTD granules were composed of Panax ginseng C.A. Meyer 9 g, Gastrodia elata 9 g, Atractylodes macrocephala 10 g, Morindae Officinalis Radix 6 g, Acorus tatarinowii Schott 6 g, Rhizoma coptidis 3 g, and Semen Cuscutae 12 g. The JTD granules are prepared in accordance with the previous methods [ 32 , 33 ]. The collected CHM was washed with water to remove any dust or foreign particles present on them and shade-dried for one week at room temperature to avoid excessive loss of volatile components.…”
Section: Methodsmentioning
confidence: 99%
“…XFC is prepared from natural medicines such as T. wilfordii, and the research and development of natural medicinal plants have been a research hotspot in this direction [29]. Molecular docking is commonly employed to simulate the binding pattern and affinity between small molecular compounds contained in natural drugs and targets [30]. The results suggested that the structure of triptolide and quercetin was stable with the key target, indicating that triptolide and quercetin may be the key active components of XFC.…”
Section: Effects Of Xfc On Joint Symptoms Inflammatory Factors and Tl...mentioning
confidence: 99%